Antitrypanosomal Effect of Hydromethanolic Extract of Solanum anguivi Lam on Field Isolates of Trypanosoma congolense Infected Mice - Debela Abdeta; Solomon Mequanente Abay; Mirutse Giday; Nigatu Kebede; Getechew Terefe (Journal of Parasitology Research)
Introduction. Trypanosomiasis is one of the world’s most serious infectious diseases caused by Trypanosoma parasites. Concern about resistance to conventional antitrypanosomal drugs, mosquito vector resistance to existing insecticide side effects of existing antitrypanosomal drugs justifies the urgent need for more effective, tolerable, and affordable drugs. Objective. The present study is aimed at determining the in vivo antitrypanosomal effect of the hydromethanolic extracts of Solanum anguivi fruit extracts against the field isolates of T. congolense. Methods. The 80% methanol extracts of S. anguivi fruits were prepared by cold maceration technique. In vivo curative tests were done to check the effect of plant extract against T. congolense in Swiss albino mice. Plant extracts were administered at doses of 100, 200, and 400 mg/kg/body weight. Acute toxicity of the extracts at 2000 mg/kg was performed according to OECD guidelines. Data obtained from the experiment were analyzed using one-way ANOVA followed by Tukey test. Results. This study indicated that extract did not exhibit any sign of acute toxicity up to 2000 mg/kg/body weight. In curative test, extracts reduced parasitemia, preventing the drop in packed cell volume and body weight significantly (p<0.05), compared to control. Groups provided with the extract before infection got prolonged incubation period with chemoprophylactic effect at the doses of 100, 200, and 400 mg/kg. Phytochemical analysis showed presence of flavonoids, steroids, triterpens, saponins, glycosides, tannins, and alkaloids. Conclusion. The extract showed promising curative. Further effort is required to isolate and purify specific compounds responsible for antitrypanosomal activity of studied plant.